Complement activation profiles in anti‐acetylcholine receptor positive myasthenia gravis. (24th February 2023) - Stascheit, Frauke; Chuquisana, Omar; Keller, Christian W.; Ambrose, Philip Alexander; Hoffmann, Sarah; Gross, Catharina C.; Lehnerer, Sophie; Wiendl, Heinz; Willcox, Nick; Meisel, Andreas; Lünemann, Jan D.
Abstract: Background and purpose: Complement component 5 (C5) targeting therapies are clinically beneficial in patients with acetylcholine receptor antibody + (AChR‐Ab + ) generalized myasthenia gravis (MG). That clearly implicates antibody‐mediated complement activation in MG pathogenesis. Here, classical and alternative complement pathways were profiled in patients from different MG subgroups. Methods: In a case–control study, concentrations of C3a, C5a and sC5b9 were simultaneously quantified, indicating general activation of the complement system, whether via the classical and lectin pathways (C4a) or the alternative pathway (factors Ba and Bb) in MG patients with AChR or muscle‐specific kinase antibodies (MuSK‐Abs) or seronegative MG compared to healthy donors. Results: Treatment‐naïve patients with AChR‐Ab + MG showed substantially increased plasma levels of cleaved complement components, indicating activation of the classical and alternative as well as the terminal complement pathways. These increases were still present in a validation cohort of AChR‐Ab + patients under standard immunosuppressive therapies; notably, they were not evident in patients with MuSK‐Abs or seronegative MG. Neither clinical severity parameters (at the time of sampling or 1 year later) nor anti‐AChR titres correlated significantly with activated complement levels. Conclusions: Markers indicative of complement activation are prominently increased in patients with AChR‐Ab MG despite standard immunosuppressive therapies. Complement inhibition proximal to C5 cleavage should be explored for its potential therapeutic benefits in AChR‐Ab + MG.